2022
DOI: 10.1101/2022.02.26.22271545
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 Exposures of Healthcare Workers from Primary Care, Long-Term Care Facilities and Hospitals: A Nationwide Matched Case-Control Study

Abstract: Objectives. Healthcare workers (HCWs) are at higher risk of contracting coronavirus disease 19 (COVID 19) than the general population. This study assessed the roles of various exposures and personal protective equipment (PPE) use on that risk for HCWs working in primary care, long term care facilities (LTCFs) or hospitals. Methods. We conducted a matched case-control (1:1) study (10 April; 9 July 2021). Cases (HCWs with confirmed COVID-19) and controls (HCWs without any COVID 19 positive test or symptoms) rec… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 27 publications
(47 reference statements)
1
6
0
Order By: Relevance
“…Similar to the findings of Belan et al 7 , a prospective cohort study at nine healthcare institutions from Switzerland found household exposure to be the strongest risk factor (adjusted hazard ratio 10.1; 95% CI 7·5−13·5) for both HCW SARS-CoV-2 swab positivity and seroconversion in a multivariate regression analysis. 11 This study also found no significant difference between the use of a filtering facepiece class 2 (FFP2) respirator versus the use of a surgical mask 11 which is consistent with the updated systematic review of observational studies for risk factors for COVID-19 among HCWs mentioned above, albeit recognizing the limitations of observational studies.…”
supporting
confidence: 84%
See 3 more Smart Citations
“…Similar to the findings of Belan et al 7 , a prospective cohort study at nine healthcare institutions from Switzerland found household exposure to be the strongest risk factor (adjusted hazard ratio 10.1; 95% CI 7·5−13·5) for both HCW SARS-CoV-2 swab positivity and seroconversion in a multivariate regression analysis. 11 This study also found no significant difference between the use of a filtering facepiece class 2 (FFP2) respirator versus the use of a surgical mask 11 which is consistent with the updated systematic review of observational studies for risk factors for COVID-19 among HCWs mentioned above, albeit recognizing the limitations of observational studies.…”
supporting
confidence: 84%
“…The matched case-control study reported by Belan et al 7 which assessed HCW COVID-19 exposures and PPE use was unique since it included HCWs working across the spectrum of healthcare delivery including acute care, long term care facilities (LTCFs) and primary care. The strengths included its large size, nationwide scope, age, sex, and regional domicile matching, timing for inclusion, and prompt contact to reduce recall bias.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to the literature, in our study the highest risk of transmission among HCWs was associated with COVID-19 contacts in the household (13-fold), where infection prevention measures may not be routinely followed and prolonged contacts at short distances occur frequently. 5,13,14,22,27,31 Household exposure was only reported by 9% of high-risk caregiver cases during the study period. This low prevalence of nonoccupational contacts might be to due underreporting associated with undetected asymptomatic infections or to the lack of benefit of occupational insurance coverage for HCWs reporting household acquisition.…”
Section: Discussionmentioning
confidence: 96%